Professionally marked components of linguistic consciousness in popular-legal internet discourse: corpus analysis - Litvishko, Olga M. (Aktualʹnye problemy filologii i pedagogičeskoj lingvistiki, 2024)
The article is devoted to the study of the verbalization specifics of professionally marked components of linguistic consciousness in popular-legal Internet discourse. On the basis of the analysis of approaches to the study of linguistic consciousness, the connection between the components of linguistic consciousness and linguistic means verbalizing its subject meanings is established. The specificity of professional linguistic consciousness, which is verbalized by professionally marked linguistic means, is revealed. The material of the study included the posts of online legal counselling sites, which serve as an example of popular-legal Internet discourse. The paper identifies the criteria that allow us to define popular-legal Internet discourse as a discourse of mixed type, which has certain features and characteristics, in particular, a specific choice of linguistic means, mixing of styles, and simplification of professional language. The author substantiates the use of linguistic means characteristic of popular-legal Internet discourse. The corpus, frequency and concordance analyses confirm the author’s hypothesis about the conditionality of a lawyer’s speech by professional language consciousness. It is established that professionally marked components of language consciousness in popular-legal Internet discourse are lexical and syntactic units that serve as a means of conveying specialized professional information, demonstrate the logic of presentation of legally significant information, despite the tendencies of simplification of the legal language. The article reveals the most frequently used linguistic means of popular legal Internet discourse, which provide storage and reproduction of lexical information and grammatical operations in speech and represent professionally marked components of linguistic consciousness in the studied type of discourse.